The epic distilled : studies in the composition of the Aeneid - Horsfall, Nicholas (Oxford University Press, 2016)
'The Epic Distilled' is a rich exploration of Virgil's use of sources in the 'Aeneid', considering elements of history, geography, mythology, and ethnography, and offering readers a fresh approach to understanding the full intellectual texture of Virgil's epic poem